(untitled) (Scientific journal of the Fergana State University, 2026)
In this work, an anion exchange material (PAN-TM) was obtained by modifying polyacrylonitrile (PAN) with thiourea (TU), and the factors affecting the process of obtaining the obtained anion exchange material were studied. Potentiometric titration was performed to determine the nature of the functional group in the newly obtained anion exchange sorbent. In order to determine the structure of the obtained anion exchanger, the IR spectra of the original and thiourea-modified polyacrylonitrile were obtained and analyzed.